2018
DOI: 10.1590/s0102-053620180107
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and quality of organic strawberries pre-harvest treated with silicon

Abstract: Mineral nutrients have important role in plant metabolism, acting on specific vital metabolic pathways for the cell. Among the nutrients, we highlight silicon (Si), for promoting growth, improving post-harvest quality and plant productivity, as well as being able to induce resistance to pest and disease. In this sense, this study aimed to evaluate the productivity and post-harvest quality of strawberry fruits cultivars Aromas and Albion cultivated in organic system with four doses of foliar applications of SiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
2
10
1
3
Order By: Relevance
“…In the 2015/2016 season, TA did not differ between AVG treatments, combined or not with ethephon, and the control. It should be noted that the SS/AT ratio represents the balance between the contents of acids and sugars in fruits, conditioned by the balance between taste and aroma (Munaretto et al, 2018). Regarding this ratio, there was no effect of pre-harvest treatments in both seasons.…”
Section: Resultsmentioning
confidence: 92%
“…In the 2015/2016 season, TA did not differ between AVG treatments, combined or not with ethephon, and the control. It should be noted that the SS/AT ratio represents the balance between the contents of acids and sugars in fruits, conditioned by the balance between taste and aroma (Munaretto et al, 2018). Regarding this ratio, there was no effect of pre-harvest treatments in both seasons.…”
Section: Resultsmentioning
confidence: 92%
“…One study reported an increase in strawberry mass (Silva et al, 2013). Meanwhile, another study reported no difference (Munaretto et al, 2018). Other studies also reported that the application of Si increased fruit yield in strawberry (Silva et al, 2013) and tomato (Marodin et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The application of Si has beneficial effects on many fruit crops, but there is still little information about the effect of Si on blueberry. The application of Si in passion fruit (Passiflora edulis) increased the photosynthetic rate of the plant (Costa et al, 2018), and in strawberry (Fragaria × ananassa) its improved pulp firmness and increased the level of anthocyanins in fruits (Munaretto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Camarosa has been reported as a highly productive cultivar, with large, firm, and tasty fruits 48 , being one of the most planted short-day cultivars in the world 49 . The presence of large number of favorable alleles in ‘Camarosa’ and ‘Aromas’ 33 and their high productive potential 50 , 51 make them promising parents for strawberry breeding programs 5 . Camargo et al 32 also found and selected the best hybrids coming from the crosses ‘Camarosa’ × ‘Aromas’ and ‘Camarosa’ × ‘Sweet Charlie’, concerning biochemical traits.…”
Section: Discussionmentioning
confidence: 99%